Role of the great toe to improve postural control in elite women handball players - Viseux, F.; Villeneuve, P.; Barbier, F.; Parreira, R.; Lemaire, A. (Neurophysiologie Clinique, 2019)
Background: Team handball is a complex intermittent sport game, which requires several, motors abilities such as sprinting, jumping, flexibility and throwing velocity. These abilities require static and dynamic control of balance. Objective evaluation of stabilometric parameters may be interesting to assess and improve functional parameters by postural control management according to the characteristics of sport activities. Objectives: To evaluate the effect of a low additional thickness placed only under the great toe on the centre of pressure (CoP) measures in elite women handball players. Methods: Fourteen elite women handball players voluntarily participated in this study. Postural oscillations were recorded for each participant using a force plate with a sampling frequency of 40 Hz over 51.2 s, and analyzed with the software coupled to the force plate. Two randomized conditions were compared: additional thicknesses under the great toe (TUGT) 0 (control) and 0.8 mm. Results: A difference with TUGT 0.8 compared to control condition was observed for the surface, the length and the average speed of CoP excursions. Conclusion: This study evidences that a low focal additional thickness placed under both great toes has an effect on the CoP measures used to assess postural control during unperturbed stance. Our results suggest that a very small additional thickness is sufficient to change CoP measures widely employed in clinical practice. These postural reactions are consistent with previous reports that used mechanical stimulation of the plantar sole. This brings perspectives in the management of athletes to prevent injury risk and optimize performance.